Doing it alone: Unisexual reproduction in filamentous ascomycete fungi. (March 2021) - Wilson, Andi M.; Gabriel, Raphael; Singer, Steven W.; Schuerg, Timo; Wilken, P. Markus; van der Nest, Magriet A.; Wingfield, Michael J.; Wingfield, Brenda D.
Abstract: Unisexuality in fungi is the result of sexual reproduction in a single isolate that harbors genes associated with only a single mating type. To date, unisexual reproduction has been described in only three genera of filamentous fungi. Consequently, our understanding of this unusual pathway is limited. In this critical review, we compare genetic, genomic and transcriptomic data from a variety of unisexual species to similar data from their primary homothallic and heterothallic relatives. These analyses show that unisexual reproduction is likely derived from heterothallism via the mutation of genes involved in the initiation of sexual reproduction. We show that significant changes in mating-type genes, pheromone precursor genes and pheromone receptor genes are common in unisexual species, but that similar changes are not evident in their primary homothallic or heterothallic relatives. These findings are particularly notable because the unisexual species are accommodated in unrelated genera, illustrating that a similar transition to unisexuality has likely occurred independently in their lineages.